2020
DOI: 10.9734/jammr/2020/v32i430400
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Spectrum and Clinical Profile of Patients Admitted with Pancytopenia

Abstract: Aims: The etiological spectrum and clinical profile of admitted patients presenting with pancytopenia were studied. Study Design: This was a prospective study conducted on 200 patients presenting to the Department of Medicine, Department of Oncology and the Allied Specialities of Medicine, Dayan and Medical College and Hospital, Ludhiana and were found to have pancytopenia during hospital stay. Results: Mean age of the patients was 45.69 ± 17.05 years with maximum number of patients (23%) in the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Thrombocytopenia was reported in 30% cases and leucopenia in 14% cases in the study. In the Dhoriya et al (20) study, found that mean Hb, WBC and platelets in 59 patients of megaloblastic anemia were 6.6 g/dL, 2,800/mm 3 and 57,492/mm 3 respectively. In our study thrombocytopenia was detected in 40 (20%), leukopenia in 34 (17%), lymphopenia in 12 (6%), neutropenia in 10 (5%).…”
Section: Discussionmentioning
confidence: 94%
“…Thrombocytopenia was reported in 30% cases and leucopenia in 14% cases in the study. In the Dhoriya et al (20) study, found that mean Hb, WBC and platelets in 59 patients of megaloblastic anemia were 6.6 g/dL, 2,800/mm 3 and 57,492/mm 3 respectively. In our study thrombocytopenia was detected in 40 (20%), leukopenia in 34 (17%), lymphopenia in 12 (6%), neutropenia in 10 (5%).…”
Section: Discussionmentioning
confidence: 94%